Sustainable Finance in Action: Evaluating Bank Mandiri Strategy and Outcomes in Indonesia - Sahabuddin, Romansyah (Universitas Negeri Makassar, 2024)
The research appraises the deployment of sustainable finance through the issuance of green bonds at Bank Mandiri in Indonesia, regarding the growing need to promote environmental sustainability and the coherence of practices in sustainable finance. This study explores how Bank Mandiri has been effective in using the issuance of green bonds as part of implementing mechanisms to increase its commitment to sustainable finance. This research uses the qualitative approach, which is also supported by a case study technique with document analysis, in-depth interviews, and participant observation in order to gain relevant data. This study illustrates how Bank Mandiri has effectively integrated green finance into its operations, fostering the growth of a green economy in Indonesia. The findings recommend that other financial institutions adopt similar strategies, and highlight the necessity for expanded research to fully understand the impacts of these practices on sustainability goals, thereby promoting the synergy between financial profitability and ecological and social responsibility.